2015
DOI: 10.1097/mib.0000000000000391
|View full text |Cite
|
Sign up to set email alerts
|

Older Age and Steroid Use Are Associated with Increasing Polypharmacy and Potential Medication Interactions Among Patients with Inflammatory Bowel Disease

Abstract: Article first published online 7 April 2015.Supplemental Digital Content is Available in the Text.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
33
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(36 citation statements)
references
References 43 publications
1
33
0
2
Order By: Relevance
“…Starting immunosuppressants or biological therapies in elderly IBD patients is often a challenge for physicians due to comorbidities and polypharmacy. Polypharmacy, reported in 44% of these patients in some cohorts, increases the risk of developing AEs due to drug interactions and errors in medication intake . Moreover, physiological changes in the elderly patients (pancreatic hypofunction, intestinal dysmotility, decreased hepatic mass and blood flow and decreased renal blood flow, and glomerular filtration rate) may impact the pharmacokinetics of orally administered drugs …”
Section: Introductionmentioning
confidence: 99%
“…Starting immunosuppressants or biological therapies in elderly IBD patients is often a challenge for physicians due to comorbidities and polypharmacy. Polypharmacy, reported in 44% of these patients in some cohorts, increases the risk of developing AEs due to drug interactions and errors in medication intake . Moreover, physiological changes in the elderly patients (pancreatic hypofunction, intestinal dysmotility, decreased hepatic mass and blood flow and decreased renal blood flow, and glomerular filtration rate) may impact the pharmacokinetics of orally administered drugs …”
Section: Introductionmentioning
confidence: 99%
“…Patients with IBD have greater use of antidepressants, sedatives, and analgesics (including narcotic analgesics) than matched controls [78]. Older patients with IBD are at increased risk of polypharmacy and potential adverse medication interactions [79]. An American study found that half of patients with CD met criteria for polypharmacy [80] and that this finding correlated with decreased quality of life and increased disease activity.…”
Section: Medication Burdenmentioning
confidence: 99%
“…Although recent literature has documented the efficacy and safety of IBD treatments in the elderly,(1318) there are substantial gaps in our understanding of the special needs and challenges of this patient population. Most clinical trials have excluded or enrolled insufficient numbers of elderly patients, significantly limiting insights into the safety and efficacy of IBD therapy as a function of age.…”
Section: Introductionmentioning
confidence: 99%